Genomic evidence of improved fertility and adaptation in Iranian domestic sheep attributed to introgression from Asiatic Mouflon and urial - Reza Khalkhali-Evrigh; Nemat Hedayat; Reza Seyedsharifi; Mirdarioush Shakouri; Eric N. Ponnampalam (Scientific Reports)
Abstract Due to the diverse climate in Iran, there has been an opportunity for the emergence of different domestic sheep breeds. On the other hand, two of the seven wild sheep species have settled in the broad areas of Iran. This study investigated the introgression between wild and domestic Iranian sheep using the whole genome sequencing data for 55 domestic and 19 wild sheep. The study reveals introgression signals from Asiatic mouflon and urial in Iranian domestic breeds. The results of Treemix unveiled the introgression from the common ancestor of Iranian domestic sheep to Asiatic mouflons, which sheds light on the dynamics of gene flow between domestic and wild sheep in Iran. There were 36 genomic regions (containing 26 protein coding genes) introgressed from both Asiatic mouflon and urial into the genome of their domestic relatives. In the genomic windows containing 19 of the mentioned genes, we observed a noticeable drop in the dxy value of the urial vs. domestic and Asiatic mouflon vs. domestic sheep. Also, a decrease in nucleotide diversity was observed in these regions for wild and domestic sheep, suggesting the occurrence of a selective sweep in the mentioned genomic regions. The study found important genes in these regions that are involved in fertility (TTC29, STPG2), spatial memory and learning (CAMK1G), taste perception (OTOP1), visual system (DYRK2) and olfactory (LOC101110674). The results demonstrate that most genes affected by introgression between wild and domestic sheep are related to survival, reproduction and adaptation. This information can enhance our understanding of the impact of wild species on domesticated livestocks, providing us with clearer insights for management, breeding, and conservation of these species.